Nickel-copper nanoflower bimetallic catalyst for depolymerization of lignin beta-o-4 bond to phenols
Patent Information
- Application Number
- CN202611157562.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-30
AI Technical Summary
本发明制备的空心炭球负载镍铜双金属催化剂具备独特纳米花片状微观形貌,双金属界面协同作用优异,能够在无外加氢气、低压惰性氛围下,定向断裂木质素及其模型化合物的β-O-4键,制备单酚类高值化学品,解决现有非贵金属催化剂团聚、积碳、醚键裂解选择性差的缺陷
[0028](1) 载体形貌与双金属协同优势突出。本发明采用硬模板法制备介孔空心炭球载体,相较于实心炭材料,内部空腔结构可缓解活性位点堵塞,同时空腔限域效应能够抑制镍铜金属颗粒迁移团聚。镍铜双金属存在明显电子转移效应,镍具备优异的醇类供氢溶剂脱氢活性,可生成活性氢以断裂β-O-4醚键。调控镍的电子结构,抑制木质素大分子二次缩合。同时水浴共沉淀制备的纳米花片状形貌,大幅暴露金属边缘不饱和活性位点,醚键活化能力提升显著。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biomass resource utilization technology, specifically relating to a method for preparing a nickel-copper nanoflower bimetallic catalyst for the depolymerization of lignin β-O-4 bonds to produce phenols. Background Technology
[0002] With the advancement of global industrialization, the consumption rate of non-renewable fossil resources such as coal and crude oil is increasing year by year, leading to increasingly prominent problems such as resource depletion, excessive carbon emissions, and air pollution. Lignocellulosic biomass has the advantages of carbon cycle neutralization, local sourcing, and vast reserves, making it the optimal choice to replace fossil aromatic hydrocarbon raw materials. As the only aromatic component in lignocellulosic biomass, lignin, with its phenylpropane polymerization framework, is the most abundant natural renewable aromatic hydrocarbon precursor in nature. However, the disordered cross-linking and dense spatial structure of lignin molecules make it prone to condensation and coking, which is the core bottleneck hindering its conversion into high-value phenolic monomers. Breakthroughs in the gentle depolymerization technology of lignin can also achieve the resource utilization of all components of lignin.
[0003] Lignin is formed by the random polymerization of three types of phenylpropane units: p-hydroxyphenyl, guaiacol, and syringyl. These units are cross-linked by various covalent bonds, among which the β-O-4 aryl ether bond accounts for more than 50% of the total linkages and has the weakest bond energy, making it the easiest chemical bond to be broken in hydrogenolysis. Current mainstream methods for lignin enhancement primarily utilize catalytic hydrogenolysis. This technology can preserve the aromatic structure while breaking bonds, making it the optimal route for preparing phenolic chemicals.
[0004] Currently, most industrial lignin byproducts come from the biorefining industry, with annual emissions in China exceeding tens of millions of tons. The vast majority of these are recovered through incineration, resulting in the complete waste of aromatic resources. Traditional high-temperature hydrogenolysis processes generally suffer from limitations in practical application. Early processes often used precious metal catalysts such as Ru and Pd, which not only resulted in high raw material procurement costs and poor resistance to poisoning, but also required a high-pressure external hydrogen system, leading to high equipment maintenance costs and significant safety risks. Furthermore, the high temperatures easily trigger secondary condensation of lignin, resulting in high viscosity and complex composition of lignin oil, making subsequent separation and purification extremely difficult, and hindering the actual yield of phenolic monomers from exceeding the upper limit.
[0005] To circumvent the drawbacks of precious metals, the industry is gradually shifting towards non-precious metal catalytic systems, with single-nickel-based porous carbon catalysts becoming a research hotspot. Nickel-based catalysts have abundant empty d-orbital electrons and excellent ability to activate ether bonds, which can significantly reduce catalyst preparation costs and is suitable for industrial-scale production. However, existing single-nickel porous catalysts have inherent drawbacks, such as the tendency of nickel nanoparticles to migrate and aggregate at high temperatures, limited dehydrogenation capabilities that require high-pressure external hydrogen, and low monomer selectivity.
[0006] To address the safety and cost drawbacks of exogenous hydrogen, catalytic transfer hydrogenolysis technology has gradually gained attention. This technology relies on in-situ dehydrogenation of alcohol solvents to supply active hydrogen, eliminating the need for external hydrogen supply. Isopropanol has become the mainstream hydrogen-donating solvent for lignin depolymerization due to its moderate dehydrogenation activation difficulty and strong chemical stability. However, pure isopropanol has a high spontaneous dehydrogenation energy barrier and low dehydrogenation efficiency at room temperature and low pressure, making it unable to independently provide sufficient active hydrogen to break the β-O-4 ether bond. Therefore, a bifunctional catalyst is required to simultaneously complete the two-step reaction of solvent dehydrogenation and ether bond cleavage.
[0007] Bimetallic synergistic modification is an effective means to optimize the catalytic performance of non-precious metals. Nickel-copper bimetals can compensate for the shortcomings of single metals through interfacial electron transfer, while the porous structure of hollow carbon spheres can inhibit metal agglomeration, and the special morphology of nanofloral patterns can maximize the exposure of edge active sites. Therefore, the development of such catalysts is of great practical significance for promoting the low-cost, green, and high-value utilization of lignin. Summary of the Invention
[0008] In view of this, the purpose of this invention is to provide a method for preparing a nickel-copper nanoflower bimetallic catalyst for the depolymerization of lignin β-O-4 bonds to produce phenols. The hollow carbon sphere-supported nickel-copper bimetallic catalyst prepared by this invention possesses a unique nanoflower-like microstructure and excellent synergistic effect at the bimetallic interface. It can directionally break the β-O-4 bonds of lignin and its model compounds under low-pressure inert atmosphere without external hydrogen, thus preparing high-value monophenolic chemicals. This overcomes the shortcomings of existing non-precious metal catalysts, such as agglomeration, carbon deposition, and poor selectivity in ether bond cleavage.
[0009] To achieve the above objectives, the present invention adopts the following technical solution:
[0010] This invention provides a nickel-copper bimetallic nanofloral catalyst, comprising a mesoporous hollow carbon sphere support and a nickel-copper bimetallic active component supported on the surface of the support. The active component, with nickel-copper metal oxide as the main active sites, grows on the surface of the carbon spheres in a two-dimensional nanofloral pattern.
[0011] The transition metal nickel accounts for 40-50 wt% of the catalyst, the transition metal copper accounts for 20-30 wt% of the catalyst, and the total loading of nickel-copper bimetallic is controlled at 60-80 wt%.
[0012] The preparation method of the nickel-copper bimetallic nano-flower-like catalyst as described above includes the following steps:
[0013] a) Ethanol, deionized water and ammonia were mixed at room temperature, and tetrapropoxysilane, resorcinol ethanol solution and formaldehyde solution were added in sequence. The mixture was polymerized at room temperature for 24 h. After high-temperature carbonization under nitrogen atmosphere, alkaline etching with sodium hydroxide solution, alternating washing with alcohol and water and vacuum drying, mesoporous hollow carbon spheres HCS were obtained.
[0014] b) Disperse the mesoporous hollow carbon spheres obtained in step a) in ethanol by ultrasonic dispersion, mix them evenly with a metal coordination aqueous solution prepared by nickel nitrate hexahydrate, copper nitrate trihydrate and hexamethylenetetramine, and perform a water bath co-precipitation reaction. After centrifugation, washing with alcohol and water and vacuum drying, the nickel-copper bimetallic precursor is obtained.
[0015] c) The nickel-copper bimetallic precursor is calcined in an air atmosphere to generate nano-flower-like nickel-copper active sites, and finally a nickel-copper bimetallic catalyst is obtained.
[0016] Preferably, the raw material ratio in step a) is: 65 mL ethanol, 15 mL deionized water, 3 mL ammonia, 3.5 mL tetrapropoxysilane, 0.4 g resorcinol, and 0.56 mL 37 wt% formaldehyde aqueous solution. Carbonization parameters: heating rate 2 ℃ / min, constant temperature holding at 700 ℃ for 4 h. Etching parameters: 2 mol / L NaOH solution, constant temperature etching at 50 ℃ for 24 h. All drying processes are performed under vacuum at 60 ℃ overnight.
[0017] Preferably, in step b), the amount of mesoporous hollow carbon spheres added is 100 mg, the volume of ethanol dispersion solvent is 30 mL, and the ultrasonic dispersion time is 30 min. The metal salt solvent is 30 mL of deionized water, and the organic ligand is hexamethylenetetramine.
[0018] Preferably, in step b), the molar ratio of nickel salt to copper salt is 1:0, 1:1, 2:1, 1:2, or 0:1, the total amount of nickel and copper metal is fixed at 1.5 mmol, and the molar ratio of nickel and copper metal to hexamethylenetetramine organic ligand is 1:2.
[0019] Preferably, in step c), the calcination environment is an air atmosphere, the calcination temperature is 500 ℃, and the calcination holding time is 2 h.
[0020] This invention provides an application of nickel-copper bimetallic nanoflower catalysts in the depolymerization of lignin and its β-O-4 type model compounds, including two schemes: catalytic hydrogenolysis of model compounds and catalytic hydrogenolysis of lignin.
[0021] Option 1: In the presence of the catalyst prepared by the preparation method described above, the lignin model compound is mixed with the hydrogen-donating solvent for hydrogenolysis to obtain the hydrogenolysis product.
[0022] Option 2: In the presence of the catalyst prepared by the above-described preparation method, lignin is mixed with a hydrogen-donating solvent for hydrogenolysis to obtain the hydrogenolysis product.
[0023] Preferably, the lignin is corn cob enzymatic hydrolysis lignin; the lignin model compound is one or more of the following compounds: 2-phenoxy-1-phenylethanol, 2-phenoxy-1-acetophenone, phenoxyethylbenzene, benzylphenyl ether, 4-benzyloxyphenol, 4-benzyloxyacetophenone, 4-benzyloxy-3-methoxyacetophenone, diphenyl ether, 4-ethylphenol, 4-propylphenol, 4-ethyl-2-methoxyphenol, 3-methoxy-4-hydroxybenzaldehyde, 2,6-dimethoxyphenol, catechol, and 3-methoxycatechol.
[0024] Preferably, the hydrogen-donating solvent is at least one of methanol, ethanol, and isopropanol. The internal standard is uniformly n-dodecane.
[0025] Preferably, the hydrogenolysis temperature of the model compound is 150~190 ℃, the reaction time is 2~6 h, the amount of hydrogen-supplying solvent is 5~30 mL, and the mass ratio of catalyst to woody model substrate is (1~5):6.
[0026] Preferably, the lignin hydrogenolysis temperature is 220 °C, the reaction time is 10 h, the amount of hydrogen-supplying solvent is 30 mL, and the mass ratio of catalyst to lignin is 1:3.
[0027] Compared with the prior art, the present invention has the following advantages:
[0028] (1) The synergistic advantages of the carrier morphology and bimetallic structure are prominent. This invention uses a hard template method to prepare mesoporous hollow carbon spheres as carriers. Compared with solid carbon materials, the internal cavity structure can alleviate the blockage of active sites, and the cavity confinement effect can inhibit the migration and aggregation of nickel-copper metal particles. Nickel-copper bimetals have obvious electron transfer effects, and nickel has excellent dehydrogenation activity in alcohol-based hydrogen-donating solvents, which can generate active hydrogen to break the β-O-4 ether bond. By regulating the electronic structure of nickel, the secondary condensation of lignin macromolecules is inhibited. At the same time, the nano-flower-like morphology prepared by water bath co-precipitation greatly exposes the unsaturated active sites at the metal edges, and the ether bond activation ability is significantly improved.
[0029] (2) The reaction conditions are mild and require no external hydrogen source. Unlike traditional precious metal or single-metal catalysts that rely on the harsh conditions of high-pressure external hydrogen, this invention uses alcohols such as isopropanol as hydrogen donor solvents, relying on catalyst activation of the solvent to produce hydrogen, significantly reducing the investment in high-pressure equipment and the safety hazards of flammability and explosion. The optimal nickel-copper ratio catalyst can achieve complete conversion of 2-phenoxy-1-phenylethanol, and the selectivity of ethylbenzene and cyclohexanol can reach 100%. For corn cob lignin, the yield can reach 79.33%, the monophenol selectivity is 87.89%, and the product purification difficulty is low.
[0030] (3) The preparation process is simple, low-cost, and highly practical. The catalyst of this invention uses nickel-copper nitrate and phenolic resin precursors as raw materials, which are inexpensive and readily available. The preferred catalyst provided by this invention exhibits excellent catalytic activity, substrate universality, and cycle stability, and has good industrialization potential in the field of lignin high-value conversion. Attached Figure Description
[0031] Figure 1 The image shows the XRD pattern of the copper-nickel bimetallic catalyst 2Ni1Cu / HCS (Cu and Ni molar ratio of 2:1) prepared in Example 1. Figure 1 (a) is the XRD pattern of the catalyst. Figure 1 (b) shows the XRD patterns before and after the 2Ni1Cu / HCS reaction.
[0032] Figure 2 XPS spectrum of the copper-nickel bimetallic catalyst 2Ni1Cu / HCS (Cu and Ni molar ratio of 2:1) prepared in Example 1. Figure 2 (a) is the XPS spectrum of the catalyst. Figure 2 (b) is the O 1s spectrum. Figure 2 (c) is the Ni 2p spectrum. Figure 2 (d) is the Cu 2p spectrum.
[0033] Figure 3 The image shows the SEM image of the copper-nickel bimetallic catalyst 2Ni1Cu / HCS (Cu and Ni molar ratio of 2:1) prepared in Example 1. Figure 3 (a) is a SEM image of HCS. Figure 3 (b) shows the SEM images before and after the 2Ni1Cu / HCS reaction.
[0034] Figure 4 The BET plot is for the copper-nickel bimetallic catalyst 2Ni1Cu / HCS (Cu and Ni molar ratio of 2:1) prepared in Example 1. Figure 4 (a) shows the N2 adsorption-desorption curves of the catalyst. Figure 4 (b) is the pore size distribution curve of the catalyst.
[0035] Figure 5 The graph shows the performance of the catalyst prepared in Example 1 on the model compound. Figure 5 (a) shows the effect of reaction temperature on the reaction. Figure 5 (b) shows the effect of reaction time on the reaction. Figure 5 (c) shows the effect of catalyst dosage on the reaction. Figure 5 (d) shows the effect of solvent type on the reaction. Figure 5 (e) shows the effect of solvent volume on the reaction. Figure 5 (f) shows the effect of the number of times the catalyst is recycled on the reaction.
[0036] Figure 6 GC-MS image of lignin reacted with the copper-nickel bimetallic catalyst 2Ni1Cu / HCS (Cu and Ni molar ratio of 2:1) prepared in Example 1.
[0037] Figure 7 The 2D HSQC spectrum of lignin is obtained by applying the copper-nickel bimetallic catalyst 2Ni1Cu / HCS (Cu and Ni molar ratio of 2:1) prepared in Example 1. Detailed Implementation
[0038] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. These embodiments are based on the technical solution of the present invention and provide detailed implementation schemes and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.
[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein in the specification of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. Percentages not explicitly stated in this invention may be considered as percentages by mass.
[0040] The specific embodiments of the present invention will be further described below with reference to the accompanying drawings and technical solutions.
[0041] Example 1
[0042] (1) Preparation of the carrier HCS: At room temperature, 65 mL of ethanol, 15 mL of deionized water, and 3.0 mL of ammonia were mixed. Then, 3.5 mL of tetrapropoxysilane (TPOS) was added to the system, and the mixture was stirred for 15 min. After the system stabilized, 2.0 mL of an ethanol solution containing 0.4 g of resorcinol and 0.56 mL of 37 wt% formaldehyde were added, and the reaction was continued to be stirred for 24 h. After the reaction was completed, the SiO2@RF nanospheres were collected by centrifugation, washed repeatedly with deionized water and ethanol, and dried overnight in a vacuum environment at 60 °C. Finally, the SiO2@RF powder was heated to 700 °C at a heating rate of 2 °C / min under a N2 atmosphere and annealed for 4 h. The obtained SiO2 / C was further treated with 2.0 M NaOH solution at 50 °C for 24 h. After centrifugation, the mixture was washed with deionized water and then dried overnight in a vacuum environment at 60 °C to obtain HCS.
[0043] (2) Preparation of NiCu / HCS catalyst: 100 mg HCS was dispersed in 30 mL of ethanol and sonicated for 30 min to obtain a uniform suspension. Separately, 1 mmol Ni(NO3)2·6H2O, 0.5 mmol Cu(NO3)2·3H2O, and 3 mmol hexamethylenetetramine (HMTA) were dissolved together in 30 mL of deionized water to form a transparent blue-green solution. The two solutions were thoroughly mixed and reacted in a water bath at 90 ℃ for 6 h. After the reaction system cooled to room temperature, the centrifugation, washing, and drying steps were repeated. Finally, the mixture was calcined in a muffle furnace at 500 ℃ (5 ℃ / min) for 2 h to obtain 2Ni1Cu / HCS.
[0044] Figure 1 The X-ray diffraction (XRD) spectra of the nickel-copper bimetallic hollow carbon sphere catalyst prepared in this embodiment are analyzed. The diffraction peaks of the single-metal Ni / HCS at 2θ = 37.96°, 43.35°, and 62.89° match those of NiO in PDF#44-1159, and the diffraction peaks of Cu / HCS at 2θ = 35.57°, 38.81°, 48.71°, and 61.45° match those of CuO in PDF#48-1548, indicating that after high-temperature calcination, the metal is mainly supported on the surface of the hollow carbon spheres in an oxidized state. The simultaneous detection of NiO and CuO diffraction peaks in 2Ni1Cu / HCS confirms successful bimetallic loading. Compared to the single-metal catalyst, the diffraction peaks of each oxide in 2Ni1Cu / HCS show slight shifts and a slight decrease in peak intensity. After the reaction, no diffraction peaks were missing from the catalyst; only minor peak position shifts occurred, indicating that no active metal was lost.
[0045] Figure 2 XPS analysis was performed on the nickel-copper bimetallic hollow carbon sphere catalyst prepared in this embodiment. The XPS overall spectrum confirmed that Ni and Cu were successfully supported on the surface of the hollow carbon spheres. The Ni 2p high-resolution spectrum showed that Ni on the catalyst surface mainly existed as NiO. After Cu doping, the characteristic peak of Ni shifted towards higher binding energies, and the Cu 2p spectrum also showed a positive peak shift, proving that there is an interfacial electronic interaction between Ni and Cu. Due to the electronegativity of oxygen, bimetallic electrons transferred to oxygen, reducing the surface electron density. The O 1s results showed that both lattice oxygen and adsorbed oxygen existed on the catalyst surface. After Cu doping, the proportion of lattice oxygen in the bimetallic catalyst increased, while the proportion of adsorbed oxygen decreased. The metal and oxygen formed a coordination structure, altering the distribution of oxygen species and the chemical environment on the surface.
[0046] Figure 3 This is a SEM analysis of the nickel-copper bimetallic hollow carbon sphere catalyst prepared in this embodiment. Figure 3 In (a), it can be clearly observed that the hollow carbon spheres exhibit good uniformity in size, approximately 200 nm. Figure 3(b) The catalyst exhibits a nanofloral pattern with a size of approximately 500 nm.
[0047] Figure 4 This section presents a BET analysis of the nickel-copper bimetallic hollow carbon sphere catalyst prepared in this embodiment. BET pore structure testing shows that the hollow carbon sphere HCS prepared by high-temperature calcination and alkaline etching possesses a large specific surface area and mesoporous structure, providing sufficient dispersion sites for the metal active components. After loading nickel and copper metals, the specific surface area and average pore size of the catalyst decrease compared to pure HCS. This is because copper particles are prone to sintering during the high-temperature preparation process, blocking the internal pores of the support and occupying the pore space.
[0048] Example 2
[0049] (1) Take 30 mg of lignin model compounds (2-phenoxy-1-phenylethanol, phenoxyethylbenzene, benzylphenyl ether, etc.), 15 mg of catalyst and 15 mL of alcohol hydrogen-donating solvent (isopropanol, methanol, ethanol, etc.) for later use;
[0050] (2) Transfer the materials from step (1) into a miniature stainless steel autoclave, seal it, purge with nitrogen for 15 minutes to remove all air from the autoclave, and then fill with nitrogen to adjust the initial pressure inside the autoclave to 1 MPa.
[0051] (3) Place the autoclave in a constant temperature heating bath, stir for a certain time, and let it cool naturally to room temperature after the reaction is complete;
[0052] (4) Collect the gaseous product and the solid-liquid mixture in the reactor separately. Separate the solid catalyst by centrifugation. Remove the metal ions by passing the liquid phase through a 0.22 μm filter membrane and simple distillation. After dilution with n-hexane, perform qualitative and quantitative analysis of the product by gas chromatography-mass spectrometry.
[0053] Comparative Example 1
[0054] Same as Example 2. In step (1) of this comparative example, the catalysts were in the ratios of n(Cu):n(Ni) = 0:1, 1:0, 1:2, 1:1, and 2:1, respectively. The model compound was 2-phenoxy-1-phenylethanol, the hydrogen donor solvent was isopropanol, and the reaction conditions were 190 °C for 4 h. The results are shown in Table 1.
[0055]
[0056] Example 3
[0057] Same as Example 2. The catalyst in step (1) has a ratio of n(Cu):n(Ni) = 2:1. The reaction temperature in step (1) is changed, while the other reaction conditions remain the same. The results are as follows. Figure 5 As shown in (a).
[0058] Example 4
[0059] Same as Example 3. The reaction temperature in step (1) is 170 °C, the reaction time in step (1) is changed, and the other reaction conditions remain unchanged. The results are as follows. Figure 5 As shown in (b).
[0060] Example 5
[0061] Same as Example 4. The reaction time was 4 hours, the amount of catalyst in step (1) was changed, and the other reaction conditions remained the same. The results are as follows. Figure 5 As shown in (c).
[0062] Example 6
[0063] Same as Example 5. The amount of catalyst used in step (1) was 10 mg, the solvent type in step (1) was changed, and the other reaction conditions remained the same. The results are as follows. Figure 5 As shown in (d).
[0064] Example 7
[0065] Same as Example 6. The hydrogen-donating solvent in step (1) is isopropanol. The amount of solvent used in step (1) is changed, while the other reaction conditions remain the same. The results are as follows: Figure 5 As shown in (e).
[0066] Example 8
[0067] Same as Example 7. The catalyst in step (1) was a recycled catalyst, and the other reaction conditions remained unchanged. The results are as follows: Figure 5 As shown in (f).
[0068] Example 9
[0069] Same as Example 8. The catalyst in step (1) was in a ratio of n(Cu):n(Ni) = 2:1, and the other reaction conditions remained unchanged. The results are shown in Table 2.
[0070]
[0071]
[0072]
[0073] Example 10
[0074] (1) Weigh 30 mg of lignin, 10 mg of 2Ni1Cu / HCS catalyst and 15 mL of isopropanol solvent, and add them together to a micro stainless steel autoclave;
[0075] (2) Purge the reactor with nitrogen for 15 minutes to remove the air inside, then fill with nitrogen and adjust the pressure to 1 MPa;
[0076] (3) Place the autoclave in a 220 ℃ constant temperature heating bath and stir for 10 h to carry out hydrogenolysis reaction. After the reaction is completed, allow it to cool naturally to room temperature.
[0077] (4) The system was centrifuged to obtain lignin oil and solid residue. The lignin oil was filtered through a 0.22 μm filter membrane to remove the catalyst, then evaporated at 45 ℃ to remove the solvent and dried at 60 ℃. The solid residue was dried at 80 ℃ to constant weight and used for subsequent yield calculation and characterization analysis. The results are shown in Table 3 and... Figure 6 As shown.
[0078] Corn cob lignin pretreatment: The lignin sample was fully dispersed in deionized water and subjected to ultrasonic-assisted treatment for 30 min at a power of 200 W and a frequency of 40 kHz to promote the desorption of impurities from the sample surface. Subsequently, vacuum filtration was performed using a sintered glass funnel, and the filter cake was repeatedly washed with deionized water until the washing solution was neutral. Finally, the solid product obtained by vacuum filtration was transferred to a 60 ℃ oven for thorough drying. After drying, it was ground into a fine powder and sealed for later use.
[0079]
[0080] Two-dimensional nuclear magnetic resonance analysis was performed on the lignin oil after lignin depolymerization.
[0081] Two-dimensional NMR analysis of lignin and depolymerized lignin in this embodiment is as follows: Figure 7 As shown, a and c are the two-dimensional NMR spectra of lignin oil, and b and d are the two-dimensional NMR spectra of lignin oil after depolymerization. The comparison confirms that the lignin linkages break during the depolymerization process, demonstrating the efficient depolymerization of lignin under the action of this catalyst.
[0082] To maximize the yield of phenolic monomers, this study systematically analyzed the effects of key process parameters on the depolymerization efficiency and product selectivity of lignin β-O-4 bonds. First, metal ratio screening revealed the synergistic advantages of nickel-copper bimetallic synthesis, while single-metal Ni / HCS and Cu / HCS exhibited low catalytic depolymerization activity. At a nickel-copper molar ratio of 2:1, the 2Ni1Cu / HCS catalytic performance reached its peak, achieving complete conversion of 2-phenoxy-1-phenylethanol at 170 °C for 4 h with 100% selectivity for the target product, thanks to the synergistic effect of the nickel-copper bimetallic interface.
[0083] Considering that the catalytic transfer hydrogenolysis reaction depends on the in-situ hydrogen donation capacity of the solvent, we further evaluated different solvent systems. Hydrogen-donating alcohol solvents can significantly improve the depolymerization effect, and the lignin monophenol product yield is the best in the isopropanol system.
[0084] Reaction temperature and time reflect both kinetic and thermodynamic limitations. Once the reaction reaches equilibrium, further increasing the temperature or extending the reaction time will trigger side reactions. Under optimal reaction conditions, this catalyst can efficiently convert lignin and exhibits excellent stability for recycling.
[0085] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made within the scope of the claims of the present invention should be included in the scope of the present invention.
Claims
1. A method for preparing a nickel-copper nanoflower bimetallic catalyst, characterized in that: Includes the following steps: a) Mix ethanol, deionized water and ammonia, then add tetrapropoxysilane, resorcinol ethanol solution and formaldehyde in sequence, polymerize at room temperature for 24 h, and obtain mesoporous hollow carbon balls after carbonization, alkaline etching, washing and drying. b) Disperse mesoporous hollow carbon spheres in ethanol and co-precipitate them with a mixture of nickel-copper salt and organic ligands in a water bath. After centrifugation, washing and drying, the metal precursor is obtained. c) The metal precursor is calcined in air to obtain the nickel-copper nanoflower bimetallic catalyst; the catalyst contains 40-50 wt% Ni and 20-30 wt% Cu.
2. The method according to claim 1, characterized in that: The raw material ratio in step a) is as follows: 65 mL ethanol, 15 mL deionized water, 3 mL ammonia, 3.5 mL tetrapropoxysilane, 0.4 g resorcinol dissolved in 2 mL ethanol, and 0.56 mL 37 wt% formaldehyde; carbonization parameters: heating rate 2 ℃ / min, holding at 700 ℃ for 4 h; alkaline etching parameters: 2 mol / L NaOH, treatment at 50 ℃ for 24 h; vacuum drying at 60 ℃ overnight.
3. The method according to claim 1, characterized in that: In step b), 100 mg of mesoporous hollow carbon spheres were dispersed in 30 mL of ethanol and sonicated for 30 min. The nickel salt was nickel nitrate hexahydrate, the copper salt was copper nitrate trihydrate, and the molar ratio of nickel salt to copper salt was 1-2:1-2. The organic ligand was hexamethylenetetramine, and the molar ratio of nickel-copper salt to organic ligand was 1:
2. The solvent was deionized water.
4. The method according to claim 1, characterized in that: In step c), the calcination temperature is 500 ℃ and the time is 2 h.
5. A nickel-copper nanoflower bimetallic catalyst prepared by the method according to any one of claims 1 to 4.
6. The application of a nickel-copper nanoflower bimetallic catalyst prepared by the method according to any one of claims 1 to 4 in the depolymerization of lignin and its β-O-4 type model compounds to prepare phenolic chemicals.
7. The application according to claim 6, characterized in that: The β-O-4 model compounds are one or more of the following: 2-phenoxy-1-phenylethanol, 2-phenoxy-1-acetophenone, phenoxyethylbenzene, benzylphenyl ether, 4-benzyloxyphenol, 4-benzyloxyacetophenone, 4-benzyloxy-3-methoxyacetophenone, diphenyl ether, 4-ethylphenol, 4-propylphenol, 4-ethyl-2-methoxyphenol, 3-methoxy-4-hydroxybenzaldehyde, 2,6-dimethoxyphenol, catechol, and 3-methoxycatechol.
